Efficacy of two rotary systems in removing gutta-percha and sealer from the root canal walls - Dadresanfar, Bahareh; Mehrvarzfar, Payman; Saghiri, Mohammad Ali; Ghafari, Sedigh; Khalilak, Zohreh; Vatanpour, Mehdi (Iranian Endodontic Journal, 2011)
INTRODUCTION: The aim of this in vitro study was to compare the efficacy of two retreatment rotary systems in removal of gutta-percha (GP) and sealer from the root canal walls with and without use of solvent. MATERIALS & METHODS: Sixty single-canalled distal roots of mandibular molars were prepared and root filled with gutta-percha and AH26. Each canal was randomly allocated to receive one of the retreatment techniques, Mtwo R or ProTaper. The groups were further divided into two subgroups: with or without the use of solvent. The cleanliness of canal walls was determined by stereomicroscope and scanning electron microscopy. RESULTS: The results showed that Mtwo R without the use of solvent was more efficient in material removal compared to ProTaper D (P<0.05). Most remnants were found in the apical third of the canals (P<0.05). CONCLUSION: Mtwo R seems to be an efficient rotary system for endodontic retreatment of root canal with GP.